Seismic vulnerability assessment of historical urban centres: case study of the old city centre in Seixal, Portugal - Ferreira, T. M.
The seismic vulnerability assessment of old masonry buildings is essential not only to buildings with recognised historical and heritage value but also to ordinary residential masonry buildings. This paper approaches the seismic vulnerability assessment of masonry buildings by applying a simplified methodology to the old city centre of Seixal in Portugal. The methodology adopted in this study was based on a vulnerability index used for the evaluation of damage and the study of loss scenarios on a large scale. Over 500 buildings were assessed using this methodology, and the results were analysed using an integrated Geographical Information System tool. The integration of the vulnerability and loss results could allow city councils or regional authorities to plan interventions based on a global view of the site under analysis, leading to more accurate and comprehensive risk mitigation strategies that support the requirements of safety and emergency planning.